STUDY OF RHIZOSPHERE BACTERIA ABILITY TO MOBILIZE Р2О5 FROM HARD-TO-ACCESS SOIL PHOSPHATES - Zakiryaeva Saidakhon I. (Web of Journals Publishing, 2024)
In this paper, the ability of 12 strains of wheat rhizosphere bacteria genus Enterobacter, Rahnella, Pantoea, Pseudomonas and Bacillus to mobilize phosphate was investigated. The strains were found to efficiently release P2O5 from tricalcium phosphate. The maximum release of P2O5 from Ca3(PO4)2 in the nutrient medium was observed on the 4th day of the experiment, ranging from 11.0 to 22.5 mg P2O5/100 ml. Phosphate-mobilizing activity was accompanied by a decrease in pH of the medium. The pH varied from the initial 7.1±0.01 to the final 4.1±0.02 during 4 days of incubation.
Keywords: Phosphorus, mobilization, rhizosphere bacteria, phosphate-mobilizing microorganisms, cultivation, optical density, pH value.